Hubungan Status Stres Psikososial Dengan Konsumsi Makanan dan Status Gizi Mahasiswa Fakultas Kedokteran Yarsi 2019 - Zahra, Mayang Ratu; Jannah, Fathul; Arsyad, Muhammad (Publikasi Indonesia, 2022)
The transition to adulthood includes physical, psychological, and psychosocial development, this is related to the nutritional status which must be monitored to identify adolescents at risk of undernutrition and excess. Nutritional problems in adolescents will seriously impact the decline in adolescent productivity. the stressors they get are from their academic life, especially from their own external needs and expectations. This study aims to determine the relationship between psychosocial stress status with food consumption and the nutritional status of 2019 FK Yarsi students. This research is an observational analytic study with a cross sectional approach which was conducted on 77 students of the class of 2019 with a total of 77 people. There is a correlation between psychosocial stress and energy consumption p = 0.000, but there is no relationship between psychosocial stress and protein consumption p = 0.638 and psychosocial stress with nutritional status p = 0.678. Higher stress will affect the level of energy consumption but not protein consumption because if protein intake exceeds the limit it will be directly oxidized, in psychosocial stress with nutritional status there is no relationship because of physical activity, balanced nutrition guidelines, clean living, monitoring, and maintaining weight.